DETERMINANTS OF VISIT TO POSYANDU WOMEN IN CEMPAKA PUTIH VILLAGE, 2022 - Enggal Nur Fadian; Isti'anah Surury; Nurfadhilah; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Coverage of under-five weighing in Indonesia has decreased from 80.8% in 2014 to 73.0% in 2015 (Ministry of Health RI, 2015). The target indicator for the percentage of districts/cities implementing active posyandu coaching in 2020 is 51%, but the results obtained by data as of January 23, 2021, are only 6%. When compared to the 2020 target, the percentage of districts/cities implementing active Posyandu training is 11.76%. This illustrates that there is still a difference of 88.24% from the indicator target that has not been met in 2021. The number of urban districts that have met the indicator criteria is 32 urban districts. This study uses a quantitative approach with a cross-sectional research design, in which all variables, both dependent and independent, will be examined at one time and simultaneously to see whether there is a relationship between the dependent variable and the independent variables from factors related to the behavior of visiting mothers under five to the posyandu in RW 04 Cempaka Putih Village, South Tangerang City. The results obtained from this study were that there were 4 variable relationships with maternal behavioral visits to posyandu from the 8 variables studied. The education variable with a p-value of 0.007 states that there is no relationship, but has an OR value of 8.360 (1.971-35.461) which states that there is a relationship in substance. The knowledge variable has a relationship with a p value of 0.000. The family support variable also has a relationship with a p value of 0.000 and the last is the variable support for health workers which states that there is a relationship with the behavior of mothers visiting the posyandu with a p value of 0.002.